Ferromagnetic resonance studies on Sm-Co/Fe thin films - (:unkn) unknown (My University, 2004)
Exchange coupling between Sm-Co and soft Fe thin films was analyzed. The exchange-spring magnet Sm-Co/Fe was divided into subatomic multilayers (d=2 A), and the spins in each layer were characterized by the average magnetization Mi, and the uniaxial anisotropy constant Ki. It was found that the easy direction for the magnetization of the hard Sm-Co layer grown on MgO(110) was not completely parallel to the sample plane but declined from the film plane by an angle of about 15°. It was observed that on increasing the static field beyond the switching value (∼5.5 KOe) for hard layer magnetization, the spectra disappeared.